Critical VAT perspectives on the treatment of settling insurance claims in the European Union in a post-Aspiro world. (2nd January 2018) - Pernet, Benoît; Gamito, Philippe
ABSTRACT: According to Article 135(1)(a) of the European VAT Directive, 'insurance and reinsurance transactions, including related services performed by insurance brokers and insurance agents' are exempt from VAT. In practice, this provision is far from being clear, and taxpayers in the insurance sector regularly face issues as to the proper scope of the exemption. The definition handed down by the Court largely focuses on the very nature of 'insurance', 'broker', and 'agent, ' and leaves, regrettably, no leeway for outsourced services to benefit from the VAT exemption. This is of particular evidence for claims handling services, which are regarded by the Court as 'back-office services' subject to VAT when performed by third parties to the insurance contract. This article considers the CJEU's jurisprudence as regards insurance claims handling services, and the 'literal and narrow' approach taken by the Court as compared to a 'market approach' in line with economic reality. It provides a view on the implementation of the Court's ruling in Belgium and in the UK, in which different VAT treatments apply in relation to claims handling services since 1 January 2018.